Partisanship and institutional trust in Mongolia. Issue 4 (18th May 2020) - Jacob, Marc S.; Schenke, Greta
ABSTRACT: What explains institutional trust in democratic institutions in Mongolia? Institutional trust facilitates establishing democratic institutions in post-transition countries and has been accounted for by institutional performance and social capital approaches in previous research. We argue that particularly in post-transition systems, partisanship, the evaluation of corruption and the quality of democracy also impacts institutional trust. To contribute to the study of political culture in Mongolia, the only Asian post-communist country to have developed towards democracy, we investigate determinants of citizens' trust in the president, parliament, and judiciary. To test the various explanatory factors of trust, we run ordered logit models using Asian Barometer data from 2014. The results suggest that, apart from institutional and social capital factors, partisanship strongly influences trust in the president and courts. This implies that Mongolians' perceptions of the justice system are informed by political preference, which partially originates in attempts to seize courts' autonomy.